Safeguarding Corporate Culture in the Hybrid Workplace - Novokhatskiy, Ilya; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This bachelor thesis delves into the complexities of maintaining a corporate culture within hybrid workplaces, a model blending remote and in-office work. As the post-pandemic world sees a surge in this work style, understanding its impact on organizational identity becomes paramount. Through a mix of qualitative and quantitative research, including interviews with HR managers and employee surveys, this study unveils the challenges posed by hybrid work to corporate culture and formulates strategies to uphold and reinforce shared values and practices. This thesis serves as a crucial guide for organizations striving to sustain their cultural essence in evolving work landscapes.
Vedoucí práce: Kateřina Legnerová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses